Investigation of the enantioselectivity of acetylcholinesterase and butyrylcholinesterase upon inhibition by tacrine-iminosugar heterodimers. (31st December 2023) - Vaaland, I. Caroline; López, Óscar; Puerta, Adrián; Fernandes, Miguel X.; Padrón, José M.; Fernández-Bolaños, José G.; Sydnes, Magne O.; Lindbäck, Emil
Abstract: The copper-catalysed azide-alkyne cycloaddition was applied to prepare three enantiomeric pairs of heterodimers containing a tacrine residue and a 1, 4-dideoxy-1, 4-imino-D -arabinitol (DAB) or 1, 4-dideoxy-1, 4-imino-L -arabinitol (LAB) moiety held together via linkers of variable lengths containing a 1, 2, 3-triazole ring and 3, 4, or 7 CH2 groups. The heterodimers were tested as inhibitors of butyrylcholinesterase (BuChE) and acetylcholinesterase (AChE). The enantiomeric heterodimers with the longest linkers exhibited the highest inhibition potencies for AChE (IC50 = 9.7 nM and 11 nM) and BuChE (IC50 = 8.1 nM and 9.1 nM). AChE exhibited the highest enantioselectivity ( ca . 4-fold). The enantiomeric pairs of the heterodimers were found to be inactive (GI50 > 100 µM), or to have weak antiproliferative properties (GI50 = 84–97 µM) against a panel of human cancer cells.